Dynamic analysis of an electromagnetic vibration absorber in a non-ideal system - Petrocino, Eduardo Abuhamad [UNESP] (2023)
A dynamic system usually used in engineering are rotating machines fixed to flexible structures, and an excessive vibration known as the Sommerfeld effect may occur in the passage of the resonance. This research aims to analyze an electromagnetic absorber in a non-ideal system, a simple model for the analysis of the first mode of a beam. In this context, an investigation of the dynamic behavior of a cantilever beam with a dc motor coupled to its free end, having an unbalanced mass on its axis, providing a non-ideal energy source. A permanent magnet is attached to this same free end, which is immersed inside a coil attached to the base. In this step, an analysis of the dynamic behavior is carried out by means of an analytical solution approximated by the averaging method and by numerical computational simulations. The absorber reduces the phenomena caused by the Sommerfeld effect and reduces the region of instability.